The Influence of Electronic Media on the Learning Process at SMPN 2 Solokan Jeruk: Pengaruh Media Elektronik terhadap Proses Pembelajaran di SMPN 2 Solokan Jeruk - Prameswari, Nandini (Edukasi: Journal of Educational Research, 2024)
Education in schools is experiencing rapid development in various aspects, including curriculum, methodology, equipment, and assessment. The curriculum implemented is increasingly dynamic, adjusted to the needs and developments of science. The learning methodology has also transformed with a new approach that is more interactive and participatory, making students more active in the teaching-learning process. This research was conducted at SMPN 2 Solokan Jeruk to examine the impact of information technology developments on the use of learning media in schools and its influence on teacher competence in teaching. The goal is to evaluate the effectiveness of technology-based media in delivering subject matter and analyze the role of four main competencies of teachers in supporting the use of innovative learning media. The hope is to find effective strategies to improve teachers' ability to design and implement engaging and interactive learning according to student needs. Electronic media has a significant and positive influence on the learning process at SMPN 2 Solokan Jeruk, and can be an effective tool to improve the quality of learning, motivation, and student skills. However, continuous evaluation and supervision are needed so that the benefits of electronic media can be felt by all students.